Transformasi Kapasitas UMKM Sektor Fashion Melalui Model Terintegrasi 3P (Production, Promotion, Payment) - Yohanes Sugiyanta; Tony Renhard Sinambela; Murdan Sianturi (Direktorat Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s fashion sector face challenges related to limited technical skills, low digital literacy, and restricted access to formal financing. This community service program aimed to strengthen the empowerment capacity of Paris Taylor MSME in Bekasi through the integrated 3P model (Production, Promotion, Payment). The program employed a Participatory Action Research (PAR) approach using a mixed-methods design implemented through the ADDIE framework over 12 weeks. The results demonstrated significant improvements in production capacity, digital marketing capability, and financial inclusion. MSME productivity increased by 75%, digital transactions expanded through e-commerce platforms, and the partner successfully obtained People’s Business Credit (KUR) financing for business development. The Integrated 3P Model proved effective in accelerating MSME transformation toward digital-based economic independence and is recommended for replication in other creative MSME sectors.